The impact of insufficient resources on the quality-of-service delivery at a primary healthcare clinic in Limpopo - Malematja, Dikeledi N.; Nkosi, Elizabeth M.; Nene, Sanele E. (Curationis (Pretoria), 2025)
Background Insufficient resources at healthcare clinics pose a serious problem, undermining the quality-of-service delivery and negatively affecting the patients as recipients of care and the staff as providers of care. The shortages often result in extended waiting periods, delayed implementation of nursing interventions, prolonged hospitalisation and the potential of increased nosocomial infections. Objectives To explore and describe the impact of insufficient resources on the quality-of-service delivery at a primary healthcare clinic in Limpopo. Method The study followed a qualitative, exploratory, descriptive and contextual design. Participants were selected using purposive sampling. Interviews were conducted until data saturation was reached. The interviews were audio-recorded, transcribed verbatim and analysed using Tesch’s eight-step method of data analysis. The study was steered by the Donabedian quality-of-care framework. Results One central theme emerged, namely scarcity of healthcare resources, with three subthemes: (1) the impact of water shortage on the quality-of-service delivery, (2) the impact of staff shortage on the quality-of-service delivery and (3) the impact of medication shortage on the quality-of-service delivery. Conclusion Insufficient resources negatively affect the quality-of-service delivery in healthcare. The provision of sufficient resources through collective managerial interventions is imperative to develop and implement measures to enhance the quality-of-service delivery. Contribution This study may create awareness among the leadership about the challenges of the clinic. It may also facilitate the development and implementation of processes to provide the resources required to improve the quality-of-service delivery.